The mass load effect on the resonant acoustic frequencies of colloidal semiconductor nanoplatelets. Issue 27 (23rd June 2016) - Girard, Adrien; Saviot, Lucien; Pedetti, Silvia; Tessier, Mickaël D.; Margueritat, Jérémie; Gehan, Hélène; Mahler, Benoit; Dubertret, Benoit; Mermet, Alain
Abstract : Downshift of nanoplatelets resonance frequencies due to ligand mass loads. Abstract : Resonant acoustic modes of ultrathin CdS and CdSe colloidal nanoplatelets (NPLs) with varying thicknesses were probed using low frequency Raman scattering. The spectra are dominated by an intense band ascribed to the thickness breathing mode of the 2D nanostructures. The measured Raman frequencies show strong deviations with respect to the values expected for simple bare plates, all the more so as the thickness is reduced. The deviation is shown to arise from the additional mass of the organic ligands that are bound to the free surfaces of the nanoplatelets. The calculated eigen frequencies of vibrating platelets weighed down by the mass of the organic ligands are in very good agreement with the observed experimental behaviours. This finding opens up a new possibility of nanomechanical sensing such as nanobalances.